Measurement of the ratio of B+c branching fractions to J/psi pi+ and J/psi mu+nu mu final states - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
The first measurement that relates semileptonic and hadronic decay rates of the B+c meson is performed using proton-proton collision data corresponding to 1.0 fb−1 of integrated luminosity collected with the LHCb detector. The measured value of the ratio of branching fractions, B(B+c→J/ψπ+)/B(B+c→J/ψμ+νμ)=0.0469±0.0028(stat)±0.0046(syst), is at the lower end of available theoretical predictions.